Effectiveness of a positive deviance approach to improve mother’s nutritional knowledge, attitude, self-efficacy, and child’s nutritional status in Maji District, West Omo Zone, South West region, Ethiopia: a cluster randomized control trial - Gizaw, Abraham Tamirat; Sopory, Pradeep; Sudhakar, Morankar (Frontiers in Public Health, 2023)
Background: Achieving appropriate feeding for infants and young children continues to be a struggle. These impediments are not only due to limited food availability but also inadequate knowledge, unfavorable attitudes, and low self-efficacy. A positive deviant approach (PDA) addressing positive and possible solutions inherent in a community focusing on problems is applied in Africa and particularly to Ethiopia. Therefore, this trial is aimed at evaluating the effectiveness of PDA in improving mothers' nutritional knowledge, attitudes, self-efficacy, and children's nutritional status.Method: This was a cluster randomized control trial in which 516 mothers were randomly assigned to either an intervention or control group after collecting baseline data. The trial participants in the intervention cluster received a positive deviant intervention for six months, whereas those in the control group received only the usual care. Trained positive deviant mothers (PDM) delivered the intervention. A pretested, structured, interviewer-administered questionnaire was used for data collection. Generalized estimating equation regression analysis adjusted for baseline covariates and clustering was used to test the intervention effect.The results showed that PDA improved breastfeeding outcomes in the intervention groups compared to their counterparts. A mean difference (MD) of breastfeeding (BF) knowledge (MD = 6.47; 95% CI: 6.45 to 6.49), BF attitude (MD = 12.68; 95% CI: 11.96 to 13.40), and BF self-efficacy (MD = 3.13; 95% CI: 3.05 to 3.21) was observed favoring the intervention. The intervention group showed better improvement in complementary feeding (CF) knowledge, attitude, and self-efficacy among mothers compared to the control group. A mean difference in CF knowledge (MD = 4.53, 95% CI: 4.31 to 4.75), CF attitude (MD = 9.14, 95% CI: 8.52 to 9.75), and CF self-efficacy (MD = 11.64, 95% CI: 11.16 to 12.12) were observed favoring the intervention. At the end of the 6-month follow-up, children in the intervention group showed a lower prevalence of underweight (18.23%) (95% CI: 4.55%, 22.54%; p = 0.004) compared with the control group.PDA was effective in improving mothers' nutritional knowledge, attitude, and selfefficacy and reducing children's underweight in the intervention area.